A Socio-Cultural Analysis of Gift Exchange from the Perspective of the Poetics of Materiality (Journal of humanities and social sciences exploratio, 2025)
As a social practice, gift exchange plays a complex and multi-dimensional role in modern society. Drawing on Marcel Mauss’s exposition of gift exchange, we can discern how the gift transcends the material level to become a social contract that sustains interdependent relationships among individuals and social responsibility: the spiritual force of the gift fosters social solidarity, and across different cultures the gift serves as a symbol of social status and prestige. Interpreting gift exchange from a cultural dimension and probing its practice and transmission in modern society can offer new perspectives for understanding social interaction and interpersonal relations. Although the forms and meanings of gift exchange have changed in modern society, its function as a key medium for emotional expression and for building social ties has become increasingly salient. At the same time, the principles of gift exchange are reflected in contemporary policy, promoting the equitable distribution of social resources and the harmony of social relations.
Keywords: gift exchange; gift; Mauss; material and culture